Determination of Mineral Composition and Phenolic Content and Investigation of Antioxidant, Antidiabetic, and Antibacterial Activities of Crocus sativus L. Aqueous Stigmas Extracts - Lemiae Zaazaa; Hanae Naceiri Mrabti; Abdelaziz Ed-Dra; Khaoula Bendahbia; Hind Hami; Abdelmajid Soulaymani; Mohammed Ibriz (Hindawi Limited, 2021)
The aim of this study is to investigate the in vitro antioxidant, antidiabetic, and antibacterial activities of Moroccan and Italian Crocus sativus (L.) stigmas extracts. The antioxidant activity was evaluated by DPPH radical scavenging assay, and the results showed that the Moroccan extract has a powerful antioxidant activity with an IC50 of 0.32 ± 0.059 μg/mL compared to the Italian extract (IC50 of 3.14 ± 0.021 μg/mL). Additionally, the antidiabetic activity was evaluated by using alpha-amylase and alpha-glucosidase inhibition assay, and both extracts showed significant antidiabetic activity. However, the antibacterial activity was evaluated by the disc diffusion method to determine the inhibitory diameters and microplate dilutions method to determine the minimum inhibitory concentration. Our findings revealed that both Moroccan and Italian extracts were more effective against Gram-positive than Gram-negative bacteria. From this study, we can conclude that the studied extracts of C. sativus are rich in natural compounds and could have a broad application in the pharmaceutical, food, and medical fields.